Implementasi Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Saintifik - Khoirun Nisa' (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2015)
Curriculum 2013 isa curriculumwhich hs many changes from the previouscurriculum that is School based(KTSP). In thecurriculum2013 employs scientific approach in the learning process. In the2013curriculumemphasizes learningSaintitikon:1. Implementation ofPAI learning(Islamic Education) whichincludes thePre-Scientificbasedlearning, Whilst learning, andthe post ofPAI (Islamic Education) - based learning2.EvaluasiScientific3. Impact ofPAI (Islamic Education) - based ScientificLearning. The result showed: Implementation of Scientific-based PAI learning in early learning in the learning materials, the learning core teachers have been conducting observing, questioning, eksploring, associating, and communicating, at the end giving follow-up activities such as homework to students. Evaluation of PAI learning that 2013 assessment of learning in the curriculum using authentic assessment that measures the competencies ranging from competence attitudes, skills, and knowledge based process not only results. Assessment is done with the authentic method, students are assessed on several aspects including daily daily tests, portfolios, observation, performance, duties and replay semester.Impact ofPAI-based learningScientificpsychologicalimpactofthisscientificare: cause a senseof responsibilityamonglearnersrespectively, strengthen thecloseness betweenstudents, teachersandstudents canwork together todiscussthe subject. Keyword : Learning, Islamic Education, Scientific